Investigating the Causes of Delay in Construction of Urban Water Supply and Wastewater Project in Water and WasteWater Project in Tehran - Shahdad Feyzbakhsh; Abdolrasul Telvari; Ali Reza Lork (Civil Engineering Journal, 2017)
It is obvious that providing drinking water in cities, especially in metropolises such as Tehran, as a political-social-economic center of the country is important. During the last decades, climatic changes, the decrease of raining, the increase of water harvesting from groundwater as well as the increase of population have intensified the importance of water in Tehran. Therefore, every change from water consumption to collecting, purifying and storing drinking water in the city reservoirs is highly critical. In the present study, the causes of delay in such projects have been determined based on experts' opinions about several concrete implemented reservoirs obtained by questionnaire and the related literature. Given to three classes pertained to such projects (employer, consultant and contractor), an initial questionnaire was provided to poll the experts' opinions and distributed among the sample of the study. In this regard, 45 Likert-scale questionnaires were equally distributed among three population; after gathering, the items with higher mean scores were selected for the main questionnaire (totally, 17 items). Using AHP method, the most important factors were identified and ranked through Expert choice Software. As the research findings revealed, failure of employer to pay to contractor timely, failure to obtaining the necessary permissions by employer before noticing to contactor to proceed, and uncertainty and buying project site by employer are the most important factors respectively.